Studi Proses Pembentukan Pendidikan Budi Pekerti Melalui Pembelajaran Agama Islam di SMA Negeri 3 Jombang - Asep Kurniawan; Suwandi (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2017)
Establishing a virtuous man is one of the aspect of national education objectives as stated in Law No. 20 of 2003, in Chapter II, Article 3 which explains that